The Effectiveness of Rehabilitation Guidance Services for Correctional Clients for Narcotics Crimes and Crime Law at the Bandung Class I Correctional Center in 2021 - Diani Indah; Yeti Rohayati (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Criminal acts in drug abuse that are already dependent are very difficult to escape from narcotics. Therefore, the problem of narcotics crimes must be handled by holding correctional client rehabilitation guidance carried out by the Bandung Class I Correctional Centre . Rehabilitation guidance carried out by the Bandung Class I Correctional Center is the process of treating and freeing addicts from dependence, a form of social protection that integrates drug addicts into social order so that they no longer abuse narcotics, and protects the community from the disturbance of crime and at the same time protects prisoners and provides provisions for a better life.  This type of research is qualitative research with a descriptive approach.  The subject of the study was the Head of General Affairs and Employees of the Bandung Class I Community Center  . The subject was taken by purposive sampling. Data collection techniques were carried out by observation, interviews and questionnaires conducted to the Head of General Affairs, Employees of the Bandung Class I Community Center and Correctional Clients for the Rehabilitation of Narcotics Crimes. Data analysis consists of data reduction, data presentation, and data verification.  The results showed that the implementation of rehabilitation guidance carried out by the Bandung Class I Correctional Center was less effective, namely from the Assisted Residents themselves.  Inhibiting factors in the correctional process include often bumping the attitude of the willingness of the Assisted Citizens who do not want to change and inadequate facilities and infrastructure.  The supporting factor or way to overcome it is that there must be a Social Worker employed to help the problems faced by the Assisted Citizens  TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//   This page is in English Translate to Indonesian    AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate English to IndonesianPRO Never translate English Never translate jurnal.unikal.ac.id